Pengaruh Adversity Quotient (AQ) Terhadap Sistem Poin Siswa MIN 7 Aceh Barat Daya - Ashariatul Fitri; Ainal Mardhiah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
Adversity quotient (AQ) is the ability of a person to face a challenge, commonly known as competitive power. According to the AQ, humans are divided into three groups, namely quitters, campers, and climbers, with low, medium, and high levels of ability. In conducting the student order, MIN 7 Southwest Aceh uses a point system where achievements and violations will be responded to with the award of points. This study was conducted to see how the Adversity Quotient (AQ) influences the Points System, whether students with a high AQ score will get a lot of points, and whether students who have a low AQ will earn a few points. The research method used is field research and library research, and the approach used is the quantitative mix method, where to know the planning and implementation of the point system, a qualitative approach is used so that the results will be described qualitatively, and to find out the influence of AQ on the point systems, a quantitative approach is used, where correlation and regression analysis will be performed for both variables, namely the variable Adversity Quotient (AQ) (X) against Student Points. (Y). As for the results obtained in this study, 72.85% of students had a "good" AQ level and 27.14% had a "low" AQ. And the Points category had 51.42% of good", 44.28% of "good," 2.85% of "sufficient", and 1.42% of less". As to the correlation result, it was "very strongly correlated", where the impact of the AQ on student points was 70%.